PBL on Learning Reading Text for Enhancing Learner’s Speaking Ability - Yudi Hari Riyanto (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2019)
This research is conducted in the teaching and learning process toward the college students during 6 meetings. The teaching and learning itself uses a reading text as one of media to enhance the learner’s speaking ability. In this case, the problems which exist in the reading text must be overcome by college students altogether. Here, the lecturer implements PBL as one of the strategy. The purposes of this research are to find out (1) how effective is the implementation of PBL on learning reading text for enhancing learner’s speaking ability, and (2) how is the learner’s activity and the result of speaking performance test during the implementation of PBL on learning reading text for enhancing learner’s speaking ability. The data were gained from observation from two observers and test given to college students in each meetings. All data were analyzed by using descriptive quantitative study. From the result of observation and test which were already obtained and calculated by researcher, it shows that the effectiveness of PBL is in high level, that is 3,96. It can be said that the learning process is effective to be implemented and for students’ activity during the implementation of PBL is also categorized high, that 3,86. Meanwhile, the result of college student’s learning achievement can also be categorized high, all students get satisfying and excellent score.